Accurate Structure Parameters for Tunneling Ionization Rates of Gas-Phase Linear Molecules - 赵松峰 栗建科 王国利 李鹏程 周效信 (Communications in theoretical physics, 2017)
In the molecular Ammosov–Delone–Krainov（MO-ADK） model of Tong et al. [Phys. Rev. A 66（2002）033402], the ionization rate depends on the structure parameters of the molecular orbital from which the electron is removed. We determine systematically and tabulate accurate structure parameters of the highest occupied molecular orbital（HOMO） for 123 gas-phase linear molecules by solving time-independent Schr¨odinger equation with B-spline functions and molecular potentials which are constructed numerically using the modified Leeuwen–Baerends（LBα）model.